2011
DOI: 10.1016/j.jomh.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding preventive behaviors among mid-Western African-American men: a pilot qualitative study of prostate screening

Abstract: Background African-American men bear a disproportionate burden for disease compared to other ethnic and racial groups. Due to gender differences in socialization and lifestyle practices, men are more likely to adopt attitudes and beliefs that undermine their health and well-being, including beliefs related to masculinity. The purpose of this study was to explore and understand the contextual factors in the attitudes and beliefs of African-American men's view of health in general, and as related to prostate can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Proximity and prominence of cancer – Participants who had seen the devastating impact of cancer among their family or friends felt acutely aware of cancer, and were prompted to undergo prostate cancer screening. [ 21 , 42 , 47 , 51 , 60 , 65 , 66 , 69 , 75 , 83 , 85 , 91 , 100 ] The death of family members due to cancer and “seeing what [they] went through”[ 51 ] as well as understanding the potential of cancer “running in the family,”[ 66 ] caused participants to become proactive about cancer screening, including for prostate cancer. Some believed their family members had cancer detected “too late”.…”
Section: Resultsmentioning
confidence: 99%
“…Proximity and prominence of cancer – Participants who had seen the devastating impact of cancer among their family or friends felt acutely aware of cancer, and were prompted to undergo prostate cancer screening. [ 21 , 42 , 47 , 51 , 60 , 65 , 66 , 69 , 75 , 83 , 85 , 91 , 100 ] The death of family members due to cancer and “seeing what [they] went through”[ 51 ] as well as understanding the potential of cancer “running in the family,”[ 66 ] caused participants to become proactive about cancer screening, including for prostate cancer. Some believed their family members had cancer detected “too late”.…”
Section: Resultsmentioning
confidence: 99%
“…9 10 Many studies have looked at factors that influence screening uptake in older men; however, few have explored young men's decision to go for screening, particularly for non-STI conditions such as high blood pressure, dyslipidaemia, obesity, smoking and alcohol. [36][37][38][39] This qualitative study therefore aimed to explore factors that influence health screening behaviour among young working men in Malaysia. Malaysia has a dualsector ( public and private) healthcare system and her population consists of different ethnic groups including Malays, Chinese, Indians and aboriginal groups.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For example, men suggested that cancer screening involving the rectum might parallel a sexual encounter and therefore, might affect or be indicative of one’s sexual orientation (Getrich et al, 2012; Harvey & Alston, 2011; Holt et al, 2009; Winterich et al, 2009). In addition, men stated that receiving a rectal examination might make them feel vulnerable to the physician performing the examination (Winterich et al, 2009; Winterich et al, 2011).…”
mentioning
confidence: 99%